2020
DOI: 10.1039/d0ta08655j
|View full text |Cite|
|
Sign up to set email alerts
|

New horizons in photocatalysis: the importance of mesopores for cerium oxide

Abstract: The world faces an imminent energy crisis. The photocatalytic H2 production reaction is a promising process for addressing this issue, obtaining renewable and clean energy. Among the studies in this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The Co 2p 3/2 peaks of CeO 2 /Co 3 O 4 at 779.3 and 781 eV correspond to Co 3+ and Co 2+ , respectively, which is similar to those of Co 3 O 4 . Benefiting from the flexible conversion of the oxidation states between Ce 3+ and Ce 4+ , CeO 2 possesses abundant oxygen vacancies in its structure, which leads to the conversion of Ce 4+ to Ce 3+ to provide electron transfer, which could improve the electronic conductivity. …”
Section: Resultsmentioning
confidence: 83%
“…The Co 2p 3/2 peaks of CeO 2 /Co 3 O 4 at 779.3 and 781 eV correspond to Co 3+ and Co 2+ , respectively, which is similar to those of Co 3 O 4 . Benefiting from the flexible conversion of the oxidation states between Ce 3+ and Ce 4+ , CeO 2 possesses abundant oxygen vacancies in its structure, which leads to the conversion of Ce 4+ to Ce 3+ to provide electron transfer, which could improve the electronic conductivity. …”
Section: Resultsmentioning
confidence: 83%
“…30 The fitting parameters were chosen according to the reported literature. 26 Due to the complexity in the Ce 3d XPS spectrum, certain constraints were applied during peak fitting. The spin-orbit split peak pairs (U 000 -V 000 , U 00 -V 00 , U 0 -V 0 , U-V, U 0 -V 0 ), i.e., Ce 3d 5/2 /Ce 3d 3/2 have an area ratio of 1.5.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hydrogenation on defective CeO 2Àx develops a novel approach to explore unique functionalities based on controlling the band-edge electronic structure through controlled manipulation of defects to make a novel photocatalyst. Recent work by Thill et al (2020) showed that CeO 2 with and without mesopores exhibits different trends in photocatalytic activity towards H 2 production in the H 2 O splitting reaction. The authors concluded that the presence of a high concentration of O vacancies enhances the photocatalytic activity of nonmesoporous CeO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal oxide nanoparticles such as TiO 2 , , SrTiO 3 , CeO 2 , Cu 2 O, and NiO are typically used in photocatalysis. In particular, SrTiO 3 is a semiconductor with a 3.2 eV band gap that, under light irradiation, can produce the hydroxyl radical (OH • ) in aqueous solutions .…”
Section: Introductionmentioning
confidence: 99%